ANALYSIS OF HEAVY METAL CADMIUM (CD) CONTENT IN THE IE SEU’UM HIT WATER AREA IN ACEH BESAR - Wahyuni, Srie; Idroes , Ghazi Mauer; Natasya, Natasya (Transpublika Publisher, 2024)
The Ie Seu'um hot springs area is located in Ie Seu'um Village, Mesjid Raya District, Aceh Besar Regency which has hot springs which are visited and used by the local community and tourists as a place for recreation with the family, a bathing place, and a place to boil food. Egg. The aim of this research is to determine and test heavy metals, namely Cadmium (Cd), which may be contained in the Ie Seu'um hot springs. The research used the AAS (Atomic Absorption Spectrophotometer) method. This research method uses a purposive sampling method, while the samples in this study were taken at spring points, namely places where people carry out egg-boiling activities and in holding tanks before the water flows into the bathing tubs. The results obtained for Cadmium (Cd) metal contained in hot springs (A) Ie Seu'um were <0.0005#) and reservoirs (B) were 0.0005#). Based on the maximum standard for Cadmium (Cd) content according to the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 in the Clean Water Requirements for heavy metals, this heavy metal does not exceed the threshold and is below the detection limit of the test method. It is hoped that the results of this research can become basic information for the public and tourists to always protect the ecosystem of the Ie Seu'um hot spring area and preserve local wisdom.